Identification of phenolic compounds, antioxidant activity and anti-cancer effects of the extract obtained from the shoots of Ornithogalum narbonense L. - Koyuncu, ć°smail; Gönel, Ataman; Akdağ, Abdurrahman; Yilmaz, Mustafa Abdullah (Cellular and Molecular Biology, 2018)
This study aimed to examine the anti-cancer and antioxidant properties and identify the phenolic content of methanol extract obtained from the shoots of the Ornithogalum narbonense L. (OR) plant, which is used for folk-medicine and food in the Sanliurfa region of Turkey. The antioxidant activity of the extract was investigated using total phenolics, flavonoids, ABTS and CUPRAC methods. Phenolic component analysis of the plant extract was performed by LC-MS/MS. The anti-cancer property of OR extract was investigated on human colon (DLD-1), endometrium (ECC-1) cancer cells and embryonic kidney (HEK-293) cells. Cytotoxic effects were defined with MTT, apoptotic activity with DNA fragmentation ELISA and AO/EB fluorescent staining, the genotixic effect with the comet assay and the intracellular oxidative status with TAS and TOS methods. As a result of the study, it was determined that OR extract showed an antioxidant effect, and as a result of the content analysis made with LC/MS-MS, phenolic components were determined, the most abundant being cosmosiin, followed by cinnamic acid, p-coumaric acid and Quinic acid. OR extract showed cytotoxic activity on DLD-1 and ECC-1 cancer cells, while the cytotoxic effect on HEK-293 cells was determined to be low. It was determined that through OR extract, by increasing the intracellular amount of free radicals on cancer cells, led to DNA damage, which consequently led to apoptosis of the cancer cells.